Multi-stage reinforced connection method for accident-resistant SiC / SiC fuel cladding tube and SiC end plug
By introducing SiC whiskers and nanowire networks into the connection layer between the SiC/SiC fuel cladding tube and the SiC terminal plug, the insufficient performance of the existing connecting layer in high dose irradiation and LOCA states is solved, and low temperatures are achieved. The connection of low thermal stress and excellent mechanical properties improves the safety and performance stability of the reactor.
Patent Information
- Application Number
- CN202310830289.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-07
AI Technical Summary
The connecting layer between the existing SiC/SiC fuel clad tube and the SiC end plug is prone to microcracks after high dose irradiation, which affects the sealing property. The connection process of the pioneer conversion ceramics has low thermal conductivity and volume shrinkage effects, resulting in force. Thermal performance is poor and it is difficult to maintain structural stability in the LOCA state.
The ceramic pioneer conversion method combined with chemical vapor deposition method was used to introduce SiC whiskers and in-situ SiC nanowire networks into the porous SiC skeleton to form a low-temperature, low-thermal stress and high mechanical properties. By regulating the encapsulant formula and process parameters Form a multi-level microstructure.
The near homogeneous connection of SiC/SiC composite materials is realized, the mechanical properties and radiation resistance of the connecting layer are improved, the structural stability in the accident state is enhanced, the radioactive substances generated by the fission of the nuclear fuel are prevented, and the reactor is improved. Safety margin.
Smart Images

Figure CN119263868A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic material connection, and in particular relates to a multi-stage strengthening connection method for an accident-resistant SiC / SiC fuel cladding tube and a SiC end plug. Background Art
[0002] As a clean baseload energy with mature technology, nuclear power has great development potential in helping to achieve the "dual carbon" goals. At present, power plant nuclear reactors and marine nuclear reactors are mainly pressurized water reactors. The fuel cladding in the pressurized water reactor can contain the nuclear fuel core, transfer the fission heat from the fuel to the coolant, and shield the radiation products of nuclear fission. Its integrity is directly related to the normal operation and service life of the pressurized water reactor, and it is one of the most important reactor safety barriers. At present, most commercial pressurized water reactor fuel claddings are made of zirconium alloy. However, zirconium alloy cladding has serious safety defects under loss of coolant accident (LOCA): metal zirconium and high-temperature water vapor react to generate hydrogen, which leads to the meltdown of the fuel cladding tube or even hydrogen explosion. Therefore, it is imperative to develop new accident-tolerant fuel cladding materials.
[0003] SiC / SiC composite materials have excellent properties such as high strength and toughness, high thermal conductivity and low thermal expansion coefficient, high neutron economy, and resistance to high-pressure hydrothermal and high-temperature water vapor corrosion. They are widely recognized as candidate materials for accident-tolerant fuel cladding in countries around the world. In actual service environments, in order to ensure the sealing of fuel elements, the SiC / SiC fuel cladding tube needs to be connected to the SiC end plug. At this time, the connection layer between the two will be a crucial factor affecting the overall performance of the component, and will often become the weak link of the SiC / SiC fuel element under normal and severe accident conditions.
[0004] At present, the main connection methods of nuclear SiC and SiC / SiC composite materials include: diffusion bonding using metals such as Mo / Ti, in-situ reaction of T-Si-C ternary system to generate MaX phase connection; NITE process using SiC nanopowder for connection; in-situ generation of glass ceramic connection and precursor conversion ceramic connection. The document "Koyanagi T, Katoh Y, Terrani K A, et al. Hydrothermal corrosion of silicon carbide joints without radiation [J]. Journal of Nuclear Materials, 2016, 481: 226-233." discloses specific embodiments of metal diffusion bonding, in-situ MAX phase bonding and NITE bonding. However, after high-dose irradiation, the metal and MAX phase connection layers will produce a series of microcracks, which will have an adverse effect on the overall sealing of the fuel element; the NITE process usually uses Al 2 O 3 , Y2 O 3 、SiO 2 As a sintering aid, its connection temperature is often as high as 1800℃, which is far higher than the operating temperature of the domestic third-generation SiC continuous fiber, which will cause damage to the fiber structure and have a negative impact on the mechanical and thermal properties of the SiC / SiC fuel cladding tube. Chinese patents (publication numbers CN110903102A, CN109336634B and CN112851389A) respectively disclose CaO-Y 2 O 3 -Al 2 O 3 -SiO 2 、CaO-MgO-Al 2 O 3 -SiO 2 and CaO-Al 2 O 3 -SiO 2 -Li 2 The invention discloses a method for connecting SiC / SiC composite materials or SiC ceramics for nuclear use with oxide glass ceramics, but the connection of oxide glass ceramics has the inherent defect of low thermal conductivity, which not only reduces the heat exchange efficiency between nuclear fuel and coolant, but also forms a great thermal stress between SiC / SiC cladding tube and SiC end plug when high heat flux density gradient acts under LOCA state. Chinese patent (publication number CN108191432B) discloses a connection process combining SiC / SiC composite screws and precursor conversion ceramics. The precursor in this process has a large amount of gas escape and leaves many pores inside the product during the cracking process, and is also accompanied by a large volume shrinkage effect, which leads to a low matrix density. Taking the above factors into consideration, in the existing precursor conversion ceramic connection process, adding or in-situ generating homogeneous filler SiC is an effective means to ensure high air tightness, excellent mechanical and thermal properties and low thermal stress of the connection layer. Summary of the invention
[0005] The present invention aims to overcome the defect of insufficient performance of the connection layer between the existing accident-resistant SiC / SiC fuel cladding tube and the SiC end plug. The present invention provides a method that combines a ceramic precursor conversion method with a chemical vapor deposition method, introduces a multi-level SiC whisker and an in-situ SiC nanowire network homogeneous with the SiC / SiC cladding tube and the SiC end plug into a porous SiC skeleton converted from a ceramic precursor, and realizes the connection between the SiC / SiC fuel cladding tube and the SiC end plug with low temperature (without damaging the SiC / SiC composite material), low thermal stress (the connection layer can maintain a high structural stability under the LOCA state) and excellent mechanical and thermal properties.
[0006] The present invention provides a multi-stage strengthening connection method for an accident-resistant SiC / SiC fuel cladding tube and a SiC end plug, comprising: (1) grinding, polishing, ultrasonically cleaning and drying the connection between the SiC / SiC fuel cladding tube and the SiC end plug; (2) SiC whiskers, SiC powder, ceramic precursor, catalyst, binder and solvent are fully mixed to obtain a paste encapsulant, wherein the ceramic precursor is at least one of polycarbosilane, polymethylsilane and polyallylcarbosilane, the catalyst is an organic compound of a transition metal, the binder is a compound of a phenolic resin and an organic silicone resin, and the volume ratio of the SiC whiskers, SiC powder, ceramic precursor, catalyst, binder and solvent is (5-25):(10-20):(10-15):(1-2):(3-6):(40-50); (3) The paste encapsulant is evenly applied to the connection surface between the SiC / SiC fuel cladding tube and the SiC end plug, and the connection layer is ceramicized and densified in a chemical vapor deposition system, thereby finally obtaining a multi-level reinforced connection layer between the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug.
[0007] Preferably, in step (1), the SiC / SiC fuel cladding tube is a SiC / SiC composite material in which third-generation SiC continuous fibers are one-dimensionally wound or two-dimensionally woven and a PyC interface, a SiC matrix and a SiC coating are deposited, with a relative density of 85-95%, an inner diameter of 7.5-10 mm and a wall thickness of 0.5-1.5 mm.
[0008] Preferably, in step (1), the relative density of the SiC end plug is 95-99%, the diameter of the part closely fitting with the cladding tube is 7.3-9.7 mm, the length is 0.5-2 cm, and the diameter of the part in contact with the external environment is 8.5-11.6 mm, and the thickness is 1-5 mm.
[0009] Preferably, in step (2), the aspect ratio of the SiC whisker is (20-50):1, the diameter is 0.2-0.5 μm, and the purity is >99%.
[0010] Preferably, in step (2), the particle size distribution of the SiC powder is 20 μm: 5 μm: 0.5 μm = 5: 3: 2, and the purity is > 99%.
[0011] Preferably, in step (2), the average relative molecular mass of the ceramic precursor is greater than 1000, and the purity is greater than 95%.
[0012] Preferably, in step (2), the transition metal in the organic compound of the transition metal is iron (thermal neutron absorption cross section 2.56 barns), chromium (thermal neutron absorption cross section 3.1 barns) or nickel (thermal neutron absorption cross section 4.49 barns), with a purity > 99%, such as dicyclopentadienyl chromium, ferrocene or di(cyclopentadienyl)nickel.
[0013] Preferably, in step (2), the mass ratio of phenolic resin to silicone resin in the binder is (1-3):1.
[0014] Preferably, in step (2), the solvent is at least one of xylene, acetone and cyclohexane, and the purity is >99%.
[0015] Preferably, in step (3), the process of ceramicizing the connecting layer includes: evacuating to 100-1000 Pa, introducing Ar at a flow rate of 50-200 mL / min, heating to 1350-1450°C at a rate of 5-10°C / min, and keeping warm for 1-5 hours to achieve ceramicization of the precursor in the connecting layer.
[0016] Preferably, in step (3), the densification process of the connecting layer comprises: maintaining a vacuum degree of 100 to 1000 Pa and an Ar flow rate of 50 to 200 mL / min, cooling to 800 to 1000° C. at a rate of 5 to 10° C. / min, selecting methyltrichlorosilane as the gas source for the SiC substrate, Ar as the diluent gas, and H 2 As a carrier gas for chemical vapor deposition; wherein the deposition time is 60 to 180 hours, the carrier gas H 2 The flow ratio of methyltrichlorosilane is (5-15):1, and the carrier gas H 2 The flow rate is 60~300mL / min.
[0017] In the present invention, the formula ratio of the encapsulant is adjusted, and the original porous SiC matrix (precursor conversion in the encapsulant) and the SiC whisker skeleton (in the encapsulant) are densified in a chemical vapor process. By precisely controlling various process parameters, a multi-level microstructure including SiC whiskers, SiC matrix and SiC nanowires is formed.
[0018] Beneficial effects:
[0019] The multi-stage strengthening connection process of the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug of the present invention has the following advantages:
[0020] (1) Nearly homogeneous bonding of SiC / SiC composites and CVD-SiC was achieved, effectively alleviating interlayer thermal stress.
[0021] (2) The connection layer from micron-sized SiC whiskers and SiC matrix to in-situ SiC nanowires has a multi-level strengthening effect, which gives it excellent mechanical properties. The morphology and volume fraction of each component are controllable, the process is simple, and the versatility is strong.
[0022] (3) Different from traditional glass sealants, it improves the radiation damage resistance of the connection layer under normal service in the reactor and the structural stability under accident conditions, effectively preventing the leakage of radioactive materials produced by the fission of nuclear fuel in the cladding tube, and improving the overall safety margin of the reactor. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a process flow chart of the present invention; Figure 2 This is a low-magnification scanning electron microscope image of the connection layer; Figure 3 This is a high-magnification scanning electron microscope image of the connecting layer (the needle-shaped ones are externally added SiC whiskers, the bamboo-shaped ones are in-situ generated SiC whiskers, and the other granular ones are SiC powders). DETAILED DESCRIPTION
[0024] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.
[0025] The following is an exemplary description of a multi-stage strengthening connection process for an accident-resistant SiC / SiC fuel cladding tube and a SiC end plug provided by the present invention (eg Figure 1 shown).
[0026] The connection between the SiC / SiC fuel cladding tube and the SiC end plug is ground, polished, ultrasonically cleaned and dried.
[0027] In an optional embodiment, the SiC / SiC fuel cladding tube is a SiC / SiC composite material in which third-generation SiC continuous fibers are one-dimensionally wound (or two-dimensionally woven) and a PyC interface, SiC matrix and SiC coating are deposited, with a relative density of 85-95%, an inner diameter of 7.5-10 mm and a wall thickness of 0.5-1.5 mm.
[0028] The relative density of the SiC end plug is 95-99%, the diameter of the part closely fitting with the cladding tube is 7.3-9.7 mm, the length is 0.5-2 cm, and the diameter of the part contacting with the external environment is 8.5-11.6 mm, the thickness is 1-5 mm. Its preparation process includes chemical vapor deposition (Braun J, Cédric Sauder, Lamon J, et al. Influence of an original manufacturing process on the properties and microstructure of SiC / SiC tubular composites[J]. Composites Part A: Applied Science and Manufacturing, 2019, 123: 170-179. DOI: 10.1016 / j.compositesa.2019.04.031.) or nano transient eutectic (Fitriani P, Sharma AS, Septiadi A, et al. Fabrication of tubular SiCf / SiC using different preform architectures by electrophoretic deposition and hot pressing[J]. Ceramics International, 2017, 43(10): 7618-7626. DOI: 10.1016 / j.ceramint.2017.03.056.).
[0029] The SiC whisker, SiC powder, ceramic precursor, catalyst, binder and solvent are fully mixed to obtain a paste encapsulant.
[0030] In an optional embodiment, the aspect ratio of the SiC whisker is (20-50):1, the diameter is 0.2-0.5 μm, and the purity is >99%; the purpose of adding SiC whiskers in the present invention is to serve as an inert reinforcement phase to improve the room temperature and high temperature mechanical properties of the connecting layer.
[0031] The particle size distribution of the SiC powder is 20 μm: 5 μm: 0.5 μm = 5: 3: 2, and the purity is greater than 99%.
[0032] The ceramic precursor is at least one of polycarbosilane, polymethylsilane and polyallylcarbosilane, and its average relative molecular mass is greater than 1000 and its purity is greater than 95%.
[0033] The catalyst is at least one of the organic transition metal compounds of iron (thermal neutron absorption cross section 2.56 barns), chromium (thermal neutron absorption cross section 3.1 barns), and nickel (thermal neutron absorption cross section 4.49 barns), with a purity of more than 99%; for example, dicyclopentadiene chromium, ferrocene, or di(cyclopentadiene) nickel are selected. The function of the catalyst is that the nano-metal particles formed by pyrolysis at high temperature serve as nucleation sites for gas-phase precursors to promote the in-situ growth of enhanced whiskers.
[0034] The binder is a compound of phenolic resin and silicone resin, and the mass ratio thereof is (1-3):1, for example, 2:1; the function of the binder is to give the connecting layer room temperature bonding strength, and the carbon and silicon produced by pyrolysis at high temperature can regulate the stoichiometric ratio of the connecting layer.
[0035] The solvent is at least one of organic solvents such as xylene, acetone, cyclohexane, etc., and the purity is greater than 99%.
[0036] The volume ratio of the SiC whisker, SiC powder, ceramic precursor, catalyst, binder and solvent is (5-25): (10-20): (10-15): (1-2): (3-6): (40-50); the advantage of the encapsulant of the present invention is that the added SiC whisker can synergistically play a reinforcing role with the in-situ generated SiC whisker to maintain the structural stability of the encapsulation connection layer under high temperature thermal shock environment.
[0037] The paste encapsulant is evenly applied to the connection surface between the SiC / SiC fuel cladding tube and the SiC end plug, and placed in a chemical vapor deposition system to ceramicize and densify the connection layer, and finally a multi-level reinforced connection layer between the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug can be obtained.
[0038] In an optional embodiment, the ceramicization and densification process of the connecting layer is as follows: evacuate to 100-1000 Pa, pass Ar at 50-200 mL / min, heat to 1350-1450° C. at 5-10° C. / min and keep warm for 1-5 hours to achieve ceramicization of the precursor in the connecting layer; then maintain the same vacuum degree and Ar flow rate, cool to 800-1000° C. at 5-10° C. / min, select MTS as the gas source of the SiC matrix, Ar as the dilution gas to control the reaction rate of chemical vapor infiltration, H 2 The MTS is brought into the chemical vapor reactor by bubbling as a carrier gas. The deposition time is 60 to 180 hours, and the carrier gas H 2 The flow ratio of the MTS is 15:1 to 5:1, and the carrier gas flow rate is 60 to 300 mL / min.
[0039] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0040] Example 1
[0041] (1) Select SiC / SiC fuel cladding tubes with a length of 10 cm, a relative density of 90%, an inner diameter of 10 mm, and a wall thickness of 0.8 mm and SiC end plugs with a relative density of 98% (specific structural parameters are as follows Figure 1 As shown), the connection between the SiC / SiC fuel cladding tube and the SiC end plug is ground, polished, ultrasonically cleaned and dried.
[0042] (2) SiC whiskers (aspect ratio of 20:1, diameter of 0.3 μm), SiC powder, polycarbosilane, dicyclopentadiene chromium, a binder (a compound of phenolic resin and silicone resin, with an effective mass ratio of 2:1) and acetone are fully mixed in a volume ratio of 25:15:10:2:3:50 to obtain a paste encapsulant.
[0043] (3) The paste encapsulant was evenly applied to the connection surface between the fuel cladding tube and the end plug, and placed in a chemical vapor deposition system to ceramicize and densify the connection layer. The specific process parameters were as follows: evacuate to 1000 Pa, pass Ar at 120 mL / min, and heat up to 1350 °C at 5 °C / min and keep warm for 1 h to achieve ceramicization of the precursor in the connection layer; then maintain the same vacuum degree and Ar flow rate, cool down to 1000 °C at 7 °C / min, select MTS as the gas source of the SiC matrix, and use Ar as the dilution gas to control the reaction rate of chemical vapor infiltration. 2 The MTS was brought into the chemical vapor reactor by bubbling as a carrier gas. The deposition time was 120 h. 2 The flow ratio of the MTS is 15:1, and the carrier gas flow rate is 180 mL / min. Finally, a multi-level strengthening connection layer of the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug can be obtained.
[0044] After testing, the thickness of the multi-level strengthening connection layer between the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug is 137μm, the thermal conductivity is 56.6W / (m·K), and the thermal expansion coefficient is 4.3×10 -6The load of the end plug push-out test is 2485N, and the load retention rate of the sample after one hot (1200℃)-cold (25℃) cycle is 79.3%.
[0045] Figure 2 This is a low-magnification scanning electron microscope image of the connecting layer. It can be seen from the image that the needle-column interlocking network structure formed is extremely uniform, without defects such as component segregation and macroscopic pores.
[0046] Figure 3 This is a high-magnification scanning electron microscope image of the connecting layer. It can be seen from the figure that the high aspect ratio needle-shaped grains are the initially introduced SiC whiskers, the bamboo-shaped high aspect ratio grains are the subsequently generated SiC whiskers in situ, and the irregular structure grains such as flaky and granular are SiC powders used as fillers.
[0047] Example 2
[0048] (1) Select SiC / SiC fuel cladding tubes with a length of 10 cm, a relative density of 85%, an inner diameter of 8.5 mm, and a wall thickness of 1.5 mm and SiC end plugs with a relative density of 95% (specific structural parameters are as follows Figure 1 As shown), the connection between the SiC / SiC fuel cladding tube and the SiC end plug is ground, polished, ultrasonically cleaned and dried.
[0049] (2) SiC whiskers (aspect ratio of 40:1, diameter of 0.2 μm), SiC powder, polyallylcarbosilane, ferrocene, a binder (a compound of phenolic resin and silicone resin, with an effective mass ratio of 2:1) and cyclohexane are fully mixed in a volume ratio of 15:10:15:1:4.5:40 to obtain a paste encapsulant.
[0050] (3) The paste encapsulant was evenly applied to the connection surface between the fuel cladding tube and the end plug, and placed in a chemical vapor deposition system to ceramicize and densify the connection layer. The specific process parameters were as follows: evacuate to 100 Pa, pass Ar at 50 mL / min, heat up to 1450 °C at 7 °C / min and keep warm for 1 h to achieve ceramicization of the precursor in the connection layer; then maintain the same vacuum degree and Ar flow rate, cool down to 900 °C at 5 °C / min, select MTS as the gas source of the SiC matrix, and use Ar as the dilution gas to control the reaction rate of chemical vapor infiltration. 2 The MTS was brought into the chemical vapor reactor by bubbling as a carrier gas. The deposition time was 60 h. 2 The flow ratio of the MTS is 5:1, and the carrier gas flow rate is 60 mL / min. Finally, a multi-level strengthening connection layer of the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug can be obtained.
[0051] After testing, the thickness of the multi-level strengthening connection layer between the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug is 164μm, the thermal conductivity is 49.7W / (m·K), and the thermal expansion coefficient is 4.9×10 -6 The load of the end plug push-out test is 2162N, and the load retention rate of the sample after one hot (1200℃)-cold (25℃) cycle is 86.4%.
[0052] Example 3
[0053] (1) Select SiC / SiC fuel cladding tubes with a length of 10 cm, a relative density of 95%, an inner diameter of 7.5 mm, and a wall thickness of 0.5 mm and SiC end plugs with a relative density of 99% (specific structural parameters are as follows Figure 1 As shown), the connection between the SiC / SiC fuel cladding tube and the SiC end plug is ground, polished, ultrasonically cleaned and dried.
[0054] (2) SiC whiskers (aspect ratio of 50:1, diameter of 0.5 μm), SiC powder, polymethylsilane, di(cyclopentadiene)nickel, a binder (a compound of phenolic resin and silicone resin, with an effective mass ratio of 2:1) and xylene are fully mixed in a volume ratio of 5:20:12.5:1.5:6:45 to obtain a paste encapsulant.
[0055] (3) The paste encapsulant was evenly applied to the connection surface between the fuel cladding tube and the end plug, and placed in a chemical vapor deposition system to ceramicize and densify the connection layer. The specific process parameters were as follows: evacuate to 500 Pa, pass Ar at 200 mL / min, and heat up to 1400 °C at 10 °C / min for 5 h to achieve ceramicization of the precursor in the connection layer; then maintain the same vacuum degree and Ar flow rate, cool down to 800 °C at 10 °C / min, select MTS as the gas source of the SiC matrix, and use Ar as the dilution gas to control the reaction rate of chemical vapor infiltration. 2 The MTS was brought into the chemical vapor reactor by bubbling as a carrier gas. The deposition time was 180 h. 2 The flow ratio of the MTS is 10:1, and the carrier gas flow rate is 300 mL / min. Finally, a multi-level strengthening connection layer of the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug can be obtained.
[0056] After testing, the thickness of the multi-level strengthening connection layer between the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug is 111μm, the thermal conductivity is 44.3W / (m·K), and the thermal expansion coefficient is 3.7×10 -6 The load of the end plug push-out test is 2793N, and the load retention rate of the sample after one hot (1200℃)-cold (25℃) cycle is 82.7%.
Claims
1. A multi-stage strengthening connection method for accident-resistant SiC / SiC fuel cladding tubes and SiC end plugs, characterized in that: include: (1) grinding, polishing, ultrasonically cleaning and drying the connection between the SiC / SiC fuel cladding tube and the SiC end plug; (2) SiC whiskers, SiC powder, ceramic precursor, catalyst, binder and solvent are fully mixed to obtain a paste encapsulant, wherein the ceramic precursor is at least one of polycarbosilane, polymethylsilane and polyallylcarbosilane, the catalyst is an organic compound of a transition metal, the binder is a compound of a phenolic resin and an organic silicone resin, and the volume ratio of the SiC whiskers, SiC powder, ceramic precursor, catalyst, binder and solvent is (5-25):(10-20):(10-15):(1-2):(3-6):(40-50); (3) The paste encapsulant is evenly applied to the connection surface between the SiC / SiC fuel cladding tube and the SiC end plug, and the connection layer is placed in a chemical vapor deposition system to perform ceramicization and densification in sequence, and finally a multi-level reinforced connection layer between the accident-resistant SiC / SiC fuel cladding tube and the SiC end plug can be obtained.
2. The connection method according to claim 1, characterized in that: In step (1), the SiC / SiC fuel cladding tube is a SiC / SiC composite material in which third-generation SiC continuous fibers are one-dimensionally wound or two-dimensionally woven and a PyC interface, SiC matrix and SiC coating are deposited, with a relative density of 85-95%, an inner diameter of 7.5-10 mm and a wall thickness of 0.5-1.5 mm.
3. The connection method according to claim 1 or 2, characterized in that: In step (1), the relative density of the SiC end plug is 95-99%, the diameter of the part closely fitting with the SiC / SiC fuel cladding tube is 7.3-9.7 mm, the length is 0.5-2 cm, and the diameter of the part in contact with the external environment is 8.5-11.6 mm, and the thickness is 1-5 mm.
4. The connection method according to any one of claims 1 to 3, characterized in that: In step (2), the aspect ratio of the SiC whisker is (20-50):1, the diameter is 0.2-0.5 μm, and the purity is >99%; the particle size distribution of the SiC powder particles is 20 μm: 5 μm: 0.5 μm = 5:3:2, and the purity is >99%.
5. The connection method according to any one of claims 1 to 4, characterized in that: In step (2), the average relative molecular mass of the ceramic precursor is greater than 1000, and the purity is greater than 95%.
6. The connection method according to any one of claims 1 to 5, characterized in that: In step (2), the transition metal in the organic compound of transition metal is iron, chromium, or nickel. Preferably, the organic compound of transition metal is dicyclopentadienylchromium, ferrocene, or di(cyclopentadienyl)nickel.
7. The connection method according to any one of claims 1 to 6, characterized in that: In step (2), the mass ratio of phenolic resin to silicone resin in the binder is (1-3):
1.
8. The connection method according to any one of claims 1 to 7, characterized in that: In step (2), the solvent is at least one of xylene, acetone and cyclohexane, and the purity is greater than 99%.
9. The connection method according to any one of claims 1 to 8, characterized in that: In step (3), the process of ceramicizing the connecting layer includes: evacuating to 100-1000 Pa, introducing Ar at a flow rate of 50-200 mL / min, heating to 1350-1450°C at a rate of 5-10°C / min, and keeping warm for 1-5 hours to achieve ceramicization of the precursor in the connecting layer.
10. The connection method according to any one of claims 1 to 9, characterized in that: In step (3), the densification process of the connecting layer includes: maintaining a vacuum degree of 100 to 1000 Pa and an Ar flow rate of 50 to 200 mL / min, cooling to 800 to 1000° C. at a rate of 5 to 10° C. / min, selecting methyltrichlorosilane as the gas source for the SiC substrate, Ar as the dilution gas, and H2 as the carrier gas for chemical vapor deposition; wherein the deposition time is 60 to 180 hours, the flow ratio of the carrier gas H2 to methyltrichlorosilane is (5 to 15): 1, and the flow rate of the carrier gas H2 is 60 to 300 mL / min.
Citation Information
Patent Citations
A method for joining SiC / SiC composite materials
CN108191432B
SiC f / SiC core-clad tube port CaO-MgO-Al2O3-SiO2 glass encapsulation method
CN109336634B
Method for encapsulating CaO-Y2O3-Al2O3-SiO2 glass at port of SiCf / SiC core cladding tube
CN110903102A
Method for connecting SiC ceramic material by using calcium oxide / aluminum oxide / silicon dioxide / lithium oxide glass solder
CN112851389A
SiC bonded ceramic matrix composite material and preparation method thereof
CN104177113A
Cited By
A SiC f Method for simultaneous densification of a base and sealing of a SiC cladding tube
CN123003309A